Biology and Control of Indian Jujube (Ziziphus mauritiana): A Weed to Watch in Florida Pastures and Natural Areas - Brent A. Sellers (EDIS)
This publication discusses the identification, habitat, ecology, spread, and control of Indian jujube. Written by Brent Sellers, and published by the UF/IFAS Agronomy Department, revised October 2021.